2012
DOI: 10.1108/17539261211250717
|View full text |Cite
|
Sign up to set email alerts
|

Green agenda and green performance: empirical evidence for real estate companies

Abstract: Purpose -A green agenda has become a growing subject throughout an increasing number of European listed real estate companies over the last decade. The focus on sustainability is presumably not only goodwill or legislation driven but is rather a benefit driven action to achieve an economic surplus. The purpose of this paper is the development of an adequate sustainability definition, the investigation of the effect of a sustainability agenda on a company level, and the identification of possible financial bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Only two of the studied companies discussed about their stakeholders and only one company outlined their stakeholders' engagement process. Caijas, Geiger, and Bienert (2012) investigated the effect of the sustainability agenda on the corporate level by studying the annual reports of 80 European listed real estate companies. Their findings show an increased level of sustainability information provision, especially in the fields of climate change, energy, social activities, and environmental aspects, and smaller increased coverage of human rights issues.…”
Section: Sustainability Reporting In the Real Estate Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Only two of the studied companies discussed about their stakeholders and only one company outlined their stakeholders' engagement process. Caijas, Geiger, and Bienert (2012) investigated the effect of the sustainability agenda on the corporate level by studying the annual reports of 80 European listed real estate companies. Their findings show an increased level of sustainability information provision, especially in the fields of climate change, energy, social activities, and environmental aspects, and smaller increased coverage of human rights issues.…”
Section: Sustainability Reporting In the Real Estate Sectormentioning
confidence: 99%
“…Third, environmental sustainability is the most common type of information reported by real estate companies in the Europe (Andelin et al, 2015; J. Willetts et al, 2011;Caijas et al, 2012). Fourth, there is no clear approach to embrace materiality, external assurance of sustainability information, and stakeholder engagement (Glass, 2012;Willetts et al, 2011;P.…”
Section: Sustainability Reporting In the Real Estate Sectormentioning
confidence: 99%
“…However, there are contradictionary opinions. While the study of 600 European companies by Albers and Gunther (2010) showed that highly capitalized companies and those adhering to sustainability indices are more likely to publish social reports, Cajias, Geiger, and Bienert (2012) demonstrated that increased media presence goes along with an increased probability of greater sustainability disclosure. Cajias and Bienert (2011) also focus on whether financial transparency determines CSR, since according to them, media visibility correlates highly with company size.…”
Section: Determinants For Sustainability Disclosurementioning
confidence: 99%
“…The first question is as to if there is innovation in real estate. Yes, definitely, one might argue: some innovations are positive such as sustainable/green buildings (Lützkendorf and Lorenz, 2006;Lorenz et al, 2007) and renewal areas (Hemphill et al, 2004a,b), CSR (Bénabou and Tirole, 2009;Cajias and Bienert, 2011;Cajias et al, 2012) or the integration of ICT into real estate (Dixon et al, 2005) 6 ; others are negative such as the harm caused by the financial engineering during the years leading to the American subprime crisis; and yet a third category of innovations can be seen as potentially either good or bad for the society, such as the application of valuation automata (see Mooya, 2011;Huff, 2014), or the establishment of real estate investment trusts (REITs, see Cajias and Bienert, 2011). The second question above is however more difficult to respond to, given the current state of disciplinary parapets.…”
mentioning
confidence: 99%
“…The last of these three traditions can be split into two converging research directions: on one hand the 'urban sustainability' (or urban biased regional sustainability) literature (e.g. Wallner et al, 1996;Bitušiková and Luther, 2010;Talen, 2011;Hoornweg et al, 2011;Joss, 2011); on the other hand the 'real estate sustainability' literature Ellison et al, 2007;Lorenz et al, 2008;Eichholz et al, 2009Eichholz et al, , 2010Fuerst and McAllister, 2011;Lützkendorf et al, 2011;Leopoldsberger et al, 2011;Cajias et al, 2012;Geiger et al, 2013). Moreover, Jones and Watkins (1996), Hemphill et al (2004a,b), Dixon (2007), Jones et al (2009), Prince's Foundation (2010, Raslanas et al (2010), and Ratcliffe et al (2010) cover elements from both traditions (and in various others) in their cross-disciplinary dealings of sustainability of real estate developments in an urban setting, as do Pareja Eastaway and Støa (2004) when combining housing and urban sustainability.…”
mentioning
confidence: 99%